2012
DOI: 10.1002/hed.23188
|View full text |Cite
|
Sign up to set email alerts
|

p16 Expression in cutaneous squamous carcinomas with neck metastases: A potential pitfall in identifying unknown primaries of the head and neck

Abstract: p16 expression is relatively common in lymph node-positive cutaneous head and neck SCCs; thus, p16 expression as an independent biomarker and mechanism to determine the oropharyngeal source of an unknown primary is not advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…According to Park et al p16 expression was only observed in OPSCC [25]. On the other hand p16 overexpression but not HPV DNA positivity was also detected in cervical lymph node metastases of squamous cell carcinomas of the skin [34]. Therefore, a positive HPV-status of the lymph node metastases in our study was defined by immunohistochemical p16 possibly allows for the avoidance of adjuvant RT or even chemoradiation to mucosal surfaces depending on the margin status and pathological features of the PT.…”
Section: Discussionsupporting
confidence: 48%
“…According to Park et al p16 expression was only observed in OPSCC [25]. On the other hand p16 overexpression but not HPV DNA positivity was also detected in cervical lymph node metastases of squamous cell carcinomas of the skin [34]. Therefore, a positive HPV-status of the lymph node metastases in our study was defined by immunohistochemical p16 possibly allows for the avoidance of adjuvant RT or even chemoradiation to mucosal surfaces depending on the margin status and pathological features of the PT.…”
Section: Discussionsupporting
confidence: 48%
“…In the absence of cystic/necrotic adenopathy, our finding of high nodal PET/CT parameters, specifically SUV max of 7.66 or higher in association with HPV+ OP SCC may be a useful tool when evaluating CUP cases as well by directing attention to the oropharynx. Although recent literature regarding CUP is somewhat contradictive 28,29 , Vent 28 reported that p16 positive nodal disease in CUP is most likely to be OP SCC.…”
Section: Discussionmentioning
confidence: 99%
“…55 HPV-RNA assessment using the E6/E7 mRNA in situ hybridization identifies transcriptionally active HPV which might be considered the gold standard for high-risk HPV detection. [64][65][66][67] Therefore, the use of p16 expression as a surrogate biomarker to OPSCC has limitations in SCCUP. 57 Immunohistochemical p16 expression as an indicator of HPV infection has gained wide popularity after the development of commercially available and low-cost antibodies.…”
Section: Pathology and Hpv Assessmentmentioning
confidence: 99%